A Muslim perspective of alternative sexual behavior - Muhsin, Sayyed Mohamed (Routledge - Taylor & Francis Group, 2026)
BDSM, an acronym for Bondage, Dominance, Sadism, and Masochism, refers to consensual practices involving power dynamics, control, and physical restraint, often aimed at erotic pleasure. While it is viewed by some as a personal sexual preference, BDSM raises significant ethical, psychological, and sociocultural concerns, especially from an Islamic perspective. This chapter seeks to explore BDSM within the framework of Islamic teachings, focusing on the three essential components of the Islamic worldview: Iman (faith), Fiqh (jurisprudence), and Akhlaq (morality). BDSM practices conflict with the maqasid al-shariah (higher objectives of Shariah), particularly in terms of intimacy, dignity, and fitrah (natural human disposition). Islamic law emphasizes the protection of life, mental health, and human dignity, all of which are compromised by BDSM due to its potential for physical harm, psychological distress, and social disruption. The concept of privacy and modesty, central to Islamic sexual ethics, is violated by acts of public display or sharing of explicit details related to BDSM. Additionally, Islam prohibits all forms of harm, even if consensual, and promotes mutual respect, love, and mercy in relationships, especially in marriage. Practices that degrade dignity, expose the ‘awrah (private parts), or violate the principles of modesty and compassion are inconsistent with Islamic values. Therefore, BDSM is generally regarded as a sexual deviation that contradicts Islamic ethics, requiring medical and psychological intervention rather than acceptance or normalization. This chapter ultimately highlights the incompatibility of BDSM with the Islamic framework of preserving the objectives of Shariah, human dignity, health, modesty, primordial human nature, privacy, the prohibition of harm, and the covering of the ‘awrah.